Compact mid-infrared graphene thermopile enabled by a nanopatterning technique of electrolyte gates. (31st August 2018) - Peng, Cheng; Nanot, Sebastien; Shiue, Ren-Jye; Grosso, Gabriele; Yang, Yafang; Hempel, Marek; Jarillo-Herrero, Pablo; Kong, Jing; Koppens, Frank H L; Efetov, Dmitri K; Englund, Dirk
Abstract: A central challenge in making two-dimensional (2D) material-based devices faster, smaller, and more efficient is to control their charge carrier density at the nanometer scale. Traditional gating techniques based on capacitive coupling through a gate dielectric cannot generate strong and uniform electric fields at this scale due to divergence of the fields in dielectrics. This field divergence limits the gating strength, boundary sharpness, and minimum feature size of local gates, precluding certain device concepts (such as plasmonics and metamaterials based on spatial charge density variation) and resulting in large device footprints. Here we present a nanopatterned electrolyte gating concept that allows locally creating excess charges by combining electrolyte gating with an ion-impenetrable e-beam-defined resist mask. Electrostatic simulations indicate high carrier density variations of Δ n ∼ 10 14 cm −2 across a length of only 15 nm at the mask boundaries on the surface of a 2D conductor. We implement this technique using cross-linked poly(methyl methacrylate), experimentally prove its ion-impenetrability and demonstrate e-beam patterning of the resist mask down to 30 nm half-pitch resolution. The spatial versatility enables us to demonstrate a compact mid-infrared graphene thermopile with a geometry optimized for Gaussian incident radiation. The thermopile has a small footprint despite the number of thermocouples in the device, paving the way for more compact high-speed thermal detectors and cameras.